2016
DOI: 10.1523/jneurosci.1480-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Toward Semantics in the Wild: Activation to Manipulable Nouns in Naturalistic Reading

Abstract: The neural basis of language processing, in the context of naturalistic reading of connected text, is a crucial but largely unexplored area. Here we combined functional MRI and eye tracking to examine the reading of text presented as whole paragraphs in two experiments with human subjects. We registered high-temporal resolution eye-tracking data to a low-temporal resolution BOLD signal to extract responses to single words during naturalistic reading where two to four words are typically processed per second. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Two recent studies (Marino et al, 2014 ; Zhang et al, 2016 ) showed a similar modulation of the motor system during the processing of objects and nouns belonging to the same category. Additionally in an fMRI study (Desai et al, 2016 ), during reading nouns expressing graspable objects activations were found in areas also involved in action performance, thus supporting a grounded view of semantics. Taken as a whole, current literature supports the notion that processing visually presented graspable objects and nouns referring to the same object category recruit common neural substrates crucially involving the motor system (Ganis et al, 1996 ; Vandenberghe et al, 1996 ).…”
Section: Introductionmentioning
confidence: 80%
“…Two recent studies (Marino et al, 2014 ; Zhang et al, 2016 ) showed a similar modulation of the motor system during the processing of objects and nouns belonging to the same category. Additionally in an fMRI study (Desai et al, 2016 ), during reading nouns expressing graspable objects activations were found in areas also involved in action performance, thus supporting a grounded view of semantics. Taken as a whole, current literature supports the notion that processing visually presented graspable objects and nouns referring to the same object category recruit common neural substrates crucially involving the motor system (Ganis et al, 1996 ; Vandenberghe et al, 1996 ).…”
Section: Introductionmentioning
confidence: 80%
“…In addition to decoding letters and words, reading involves readers’ experiences, including multimodal integration of linguistic and nonlinguistic knowledge involved in meaning construction. Early evidence suggests that “experiential and linguistically acquired knowledge can be detected in brain activity elicited in reading natural sentences” (Anderson et al, 2019, p. 8969), in contrast to reading lists of words or pseudowords (Desai, Choi, Lai, & Henderson, 2016). In short, naturalistic reading activates the same sensorimotor systems as nonlinguistic experiences.…”
Section: A Confluence Of Complexitymentioning
confidence: 99%
“…At the same time, our study carries an important methodological implication for handwriting studies in general: Given that fine‐grained semantic aspects of the target words can modulate writing kinematics, it seems crucial to control the ratio of action‐to‐non‐action words in an experiment’s stimulus sets, as gross outcomes could be partially driven by inconspicuous embodied effects differing between conditions. Moreover, this consideration could be contemplated in future studies extending our paradigm beyond the single‐word level, so as to explore language‐embodiment effects on more realistic linguistic materials (Desai et al, ; GarcĂ­a et al, ; Trevisan et al, ).…”
Section: Limitations and Avenues For Further Researchmentioning
confidence: 99%